2018
DOI: 10.1063/1.5019146
|View full text |Cite
|
Sign up to set email alerts
|

Effective macroscopic description for heat conduction in periodic composites

Abstract: Abstract. The investigation of solutions to heat transfer problems in periodic composites very often lead to the development of a certain extension of tolerance modelling to the case in which the role of shape functions is fulfilled by elements of a certain orthogonal Fourier basis. We are to show how establish such kind of extension and apply obtained result to formulate the homogenized description of heat transfer processes. Considerations are illustrated by the formulation of approximated solutions to the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…We can mention here also a series of papers where problems of heat conduction were analysed, e.g. [9,8,19,21,24]. In the books edited by Woź niak et al [26,28] the extended list of references on this subject can be found.…”
Section: Introductionmentioning
confidence: 99%
“…We can mention here also a series of papers where problems of heat conduction were analysed, e.g. [9,8,19,21,24]. In the books edited by Woź niak et al [26,28] the extended list of references on this subject can be found.…”
Section: Introductionmentioning
confidence: 99%